Optimisme menghadapi masa pensiun : Bagaimana peranan psychological well being? - Silvia Mega Puspita; Tatik Meiyuntariningsih; Akta Ririn Aristawati (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between psychological well-being and optimism for retirement. The hypothesis put forward is that there is a positive relationship between psychological well-being and optimism for retirement. This study uses a correlational quantitative research method. Sampling using one of the types of non-probability sampling technique, namely snowball sampling. This study involved 72 retired civil servants/private employees with age criteria of 55-65 years and had been retired for <1 - 5 years. The instruments used in this study are the optimism scale which refers to Seligman's theory (2008) and the psychological well being scale which refers to Ryff's theory (1989). The data analysis technique using product moment correlation shows that rxy = 0.266 with a significance level of 0.012. This means that there is a positive relationship between psychological well-being and optimism for retirement. So that the higher the psychological well being, the higher the optimism that individuals have for retired employees. Vice versa, the lower the psychological well-being, the lower the individual's optimism for retired employees. Keywords: psychological well being, optimism, retirement Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara psychological well being dengan optimisme menghadapi masa pensiun. Hipotesis yang diajukan adalah ada hubungan positif antara psychological well being dengan optimisme menghadapi masa pensiun. Penelitian ini menggunakan metode penelitian kuantitatif korelasional. Pengambilan sample menggunakan salah satu dari jenis teknik non probability sampling yaitu snowball sampling. Penelitian ini melibatkan sebanyak 72 pensiunan pegawai negeri dan swasta dengan kriteria usia 55-65 tahun dan telah pensiun selama <1 - 5 tahun. Instrumen yang digunakan dalam penelitian ini adalah skala optimisme yang mengacu pada teori Seligman (2008) dan skala psychological well being yang mengacu pada teori Ryff (1989). Teknik analisis data menggunakan korelasi product moment menunjukkan bahwa rxy = 0,266 dengan taraf signifikansi 0,012. Artinya terdapat hubungan positif antara psychological well being dengan optimisme menghadapi masa pensiun. Sehingga semakin tinggi psychological well being maka semakin tinggi optimisme yang dimiliki individu pada pensiunan pegawai. Begitupun sebaliknya, semakin rendah psychological well being maka semakin rendah optimisme yang dimiliki individu pada pensiunan pegawai. Kata kunci: psychological well being, optimisme, masa pensiun